Aesthetics as an Aspect of Good in Enderby Novels by Anthony Burgess - Smyslova, Ekaterina V.; Khabibullina, Liliya F. (Journal of History Culture and Art Research, 2017)
This article considers the interaction of ethics and aesthetics in A. Burgess’s worldview. It is based on an analysis of the novels about the minor poet Enderby, who is interpreted as the writer’s alter ego. The material for the article is represented by the novels "Inside Mr. Enderby", "Enderby outside", "The Clockwork Testament, or Enderby’s End", "Enderby’s Dark Lady", or "No End of Enderby". Particular attention is paid to the personality of the protagonist and his worldview. In the course of the analysis, the superficial interpretations of Enderby’s image and the system of his relationships with the outside world are rejected in favor of deeper ones, arising from the system of the author’s outlooks on creativity. The material of other writer’s novels is also attracted to the study ("A Clockwork Orange", "The Wanting Seed", "Little Wilson and Big God", etc), where his religious and ethical views are most clearly manifested. The analysis of Burgess’s search for faith, his path from congenital Catholicism through Manichaeism to the development of his own religious and ethical picture of the world has been performed in this paper. It has shown that according to Burgess the Beauty is of primary value and the writer is seen as the creator of such a world view where the original duality of reality can be overcome through the language.